Pengaruh Pertumbuhan Aset dan Beban Bunga terhadap Profit Bank Milik Pemerintah Indonesia - Syaputri, Ayu Geby Gisela (LPPM Universitas Multi Data Palembang, 2024)
The purpose of this study was to determine the effect of asset growth and interest expense on the profit of Indonesian state-owned banks. The observation period is from January to December 2022. This study uses multiple regression analysis. In this study it was concluded that asset growth had a negative and significant effect on the profits of Indonesian state-owned banks, while interest expense had a positive and significant effect on the profits of Indonesian government-owned banks.